Pengaruh Strategi Pembelajaran dan Bentuk Tes Formatif Terhadap Hasil Belajar Matematika Dengan Mengontrol Intelegensi Siswa - Lizza Novrida (Jurnal Pendidikan dan Kebudayaan, 2010)
The objectives of this study is to find out the effects of the learning strategy and the formative test on the learning outcome in mathematics. The quasi-experiment with 2x2 factorial design was used in this research. A cluster random sampling was used for 80 students of grade-2 at the State Junior High Schools number 11 and 19 in Jakarta in 2009-2010. The independent variables were the learning strategy and formative test, and for the dependent variables were learning outcome. The student intelligent was used as a co-variable. The strategy used were the information mapping, and conventional strategy, and the test were multiple choice and essay. The results showed the fallowings: 1) the information mapping strategy is more effective than the conventional way; 2) the multipl choice is better than essay test; 3) there was found an interaction between the learning strategy with the formative test.Â ABSTRAKPenelitian ini bertujuan menemukan pengaruh strategi pembelajaran dan bentuk tes formatif terhadap hasil belajar matematika dengan mengontrol inteligensi siswa. Penelitian ini menggunakan design eksperimen faktorial 2x2. Cluster random sampling dengan 80 siswa kelas delapan di SMPN 11 dan SMPN 19 Jakarta pada tahun ajaran 2009/2010. Variabel bebasnya yaitu strategi pembelajaran dan bentuk tes formatif, serta variabel terikatnya hasil belajar matematika. Inteligensi sebagai co-variabel. Strategi yang digunakan yaitu pemetaan informasi dan konvensional, dan bentuk tes formatif yang digunakan adalah pilihan ganda dan uraian. Hasil penelitian menunjukkan: 1) strategi pemetaan informasi lebih efektif dibanding strategi konvensional; 2) bentuk tes formatif pilihan ganda kurang efektif dibanding bentuk tes formatif uraian, dan 3) terdapat interaksi antara strategi pembelajaran dengan bentuk tes formatif.